Evaluation of Mechanical Properties of Damascus Steel - Adrián Židzik (UIKTEN, 2021)
This article deals with examination of the mechanical properties of Damascus steel. Damascus steel is steel used for blades or knives – similar to the past (Damascus steel was a type of steel used for blades in the Near East – made from wootz steel – imported from India). This steel is characterized by significant patterns. The aim of the present study is to point out the laborious method of Damascus production, and to compare the mechanical properties of the initial Damascus steel layers comparison with whole reference Damascus material steel itself.